The Small Business as Viewed by Entrepreneurs: the Dynamics of the Problems Importance Evaluation in Crises Periods - A. V. Sukhoparova (Управленческие науки)
The article analyses the data about two sociological investigations of small and medium enterprises in the Yaroslavl region in 2008-2009 and 2014-2015 crises periods in order to compare the degrees of problems importance facing them in each period. Approximately 500 enterprises and individual entrepreneurs working in all the branches of region economy accessible for SMB are the object of the investigation. In the result of the respondents’ questionnaires comparative analysis the positive dynamics in legislation vision by small and medium business subjects has been detected, but entrepreneurs attitude towards the legislation quality is likely to be negative. The tax legislation amendments in between crises period have shown the positive dynamics of entrepreneurs’ vision. However as viewed by entrepreneurs small business subjects still need in Government support and the ways of which are not efficient enough. In the result of research the conclusion is made about the necessity of differentiating measures to support small and medium business subjects.